Acompañamiento empresarial a los microempresarios suscritos al proyecto Empresarios S.O.S Actuar Famiempresas (2016)
“Empresarios S.O.S” is a program of business strengthening microfinance institution belonging to the Actuar famiempresas. This program was founded in 2011 in response to high mortality rates presented in the microenterprise sector of the department of Quindio. However “Actuar Famiempresas” increased its coverage advice to the municipalities of Dosquebradas (Risaralda) and Cartago (Valle). This program is responsible for providing business advice for free to micro-entrepreneurs evidencing problems threatening the existence of their business. The team of Empresarios S.O.S program. it is composed of an area coordinator and a student of business administration from the University of Quindío in each of the venues where the institution is located. The coordinator is responsible for assessing administrative processes, professionally supports the student as an intern and evaluates the outcome of each of the advice made by the program. Similarly, the student is responsible for providing a consultancy according to the situation in which the production unit or small business is located. In this advice the student submits a micro-entrepreneurs administrative tools so that this person executes them in their business and thus can improve the current state of your micro or productive unit. Similarly, the student will be watching the microentrepreneurs make good use of these tools by tracking and control is performed three months after the acceptance of the advice by the small businessman.